Enhancing microwave heating uniformity using reconfigurable diffractive beamforming surface. Issue 1 (7th September 2021) - Kim, Daehyeon; Kim, Minhyeock; Youn, Youngno; Chang, Suho; Lee, Cheonga; Kim, Jeongwon; Oh, Bukuk; Hong, Wonbin
Abstract: Conventional microwave oven suffers nonuniform electric field distribution due to standing wave inside the cavity, requiring improved heating uniformity. Multimode ovens, which are regarded as the most popular method, suffer from relatively limited accuracy and dependency on experimental validations. In this paper, a new class of microwave heating methodology is proposed to achieve heating uniformity improvements through the suppression of undesired standing waves. Microwave absorbers and focusing of electromagnetic waves using reconfigurable diffractive surface are devised, validated, and discussed. Numerical and experimental studies ascertain that the heat uniformity is improved by more than three factors compared to conventional microwave applicators, indicating its potential application and feasibilities.